Real time fault injection using enhanced OCD - a performance analysis - André V. Fidalgo (2006)
Fault injection is frequently used for the verification and validation of dependable systems. When targeting real time microprocessor based systems the process becomes significantly more complex. This paper proposes two complementary solutions to improve real time fault injection campaign execution, both in terms of performance and capabilities. The methodology is based on the use of the on-chip debug mechanisms present in modern electronic devices. The main objective is the injection of faults in microprocessor memory elements with minimum delay and intrusiveness. Different configurations were implemented and compared in terms of performance gain and logic overhead.